HUBUNGAN POLA KOMUNIKASI ORANG TUA DENGAN PENGETAHUAN DAN SIKAP KESEHATAN REMAJA DI DESA LANGA KECAMATAN SYAMTALIRA BAYU KABUPATEN ACEH UTARA - Fatiyani; Erlina; Yenny Fitri Wahwuni (Jurnal Cakrawala Ilmiah, 2023)
In Indonesia, 2.6% of first marriages are carried out at the age of less than 15 years and 23.9% of first marriages are aged 15-19 years. The pregnancy rate for adolescents aged less than 15 years is 0.02% and pregnancies at the ages of 15-19 years is 1.97%. This figure shows that adolescents' awareness of the importance of reproductive health knowledge is still low. Communication between parents and adolescents regarding reproductive health is very important, especially in reducing risky sexual behavior. The design of this study uses a quantitative descriptive analytical method. The instrument used is a questionnaire. The population is adolescents aged 10-19 years who live in Langa Village, Syamtalira Bayu, North Aceh. The sample size was calculated using the Solvin formula, totaling 30 people. The results of the chi-square test statistic between parents' communication patterns and adolescents' knowledge about adolescent health obtained a value of p = 0.001, then the p value <α 0.05 means that H0 is rejected, so there is a relationship between parents' communication patterns and adolescent health knowledge. The test results between parents' communication patterns and adolescent health attitudes obtained p = 0.001, so the p value <α 0.05 means that H0 is rejected. There is a relationship between parental communication patterns and adolescent health attitudes. This shows that adolescents who have difficulty communicating with parents about reproductive health, adolescents tend to have less attitude towards reproductive health, open discussion about sexuality becomes difficult for parents and adolescents because of social and cultural taboos. Parents should be the primary source of information and educators